2014
DOI: 10.7895/ijadr.v3i2.178
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol’s harm to others: Using qualitative research to complement survey findings

Abstract: Aim: The purpose of this study was to identify the potential contribution of qualitative research to future Alcohol's Harm to Others (AHTO) survey research and some of the potential difficulties that may be encountered when conducting studies of this nature.Design: Qualitative, in-depth semi-structured telephone interviews.Setting: Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…Moreover, future studies would benefit from specifying the harms from others' use of the three substances, preferably using a qualitative approach to identify the significant harms (e.g., physical, psychological) and then investigate the prevalence of the identified harms using surveys (for examples of studies combining survey data and qualitative data, see Manton, MacLean, Laslett, & Room, 2014;Scheffels et al, 2016). Further, to examine the possible impact of self-reported harm from others' substance use on health, survey data could be combined with registry data on health-related outcomes such as depression, anxiety and sickness absence, as well as substance-use problems (Lund et al, 2015;Rossow, 2015;Rossow & Ramstedt, 2016).…”
Section: Methodological Considerations and Suggestions For Future Resmentioning
confidence: 99%
“…Moreover, future studies would benefit from specifying the harms from others' use of the three substances, preferably using a qualitative approach to identify the significant harms (e.g., physical, psychological) and then investigate the prevalence of the identified harms using surveys (for examples of studies combining survey data and qualitative data, see Manton, MacLean, Laslett, & Room, 2014;Scheffels et al, 2016). Further, to examine the possible impact of self-reported harm from others' substance use on health, survey data could be combined with registry data on health-related outcomes such as depression, anxiety and sickness absence, as well as substance-use problems (Lund et al, 2015;Rossow, 2015;Rossow & Ramstedt, 2016).…”
Section: Methodological Considerations and Suggestions For Future Resmentioning
confidence: 99%
“…[ 1 5 6 ] Female children were more likely to report alcohol-related violence and problems at home; males were more likely to report assaults, property damage, and violence in the street. [ 10 11 12 13 14 ] A qualitative study of caregivers reported that children exposed to alcohol harm had greater shame, social withdrawal, anxiety, and poorer academic performance. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…If this association to some extent reflects causality, possible underlying mechanisms may include accumulation of numerous minor harms, as described above. One possible way to further investigate this issue is to supplement survey data with qualitative studies, in line with Manton and co-workers(Manton, MacLean, Laslett, & Room, 2014).…”
mentioning
confidence: 99%